Trapping and Manipulation of Single Cells in Crowded Environments - Zhao, Qian; Wang, Hao-Wei; Yu, Pan-Pan; Zhang, Shu-He; Zhou, Jin-Hua; Li, Yin-Mei; Gong, Lei (Frontiers in Bioengineering and Biotechnology, 2020)
Optical tweezers provide a powerful micromanipulation tool in vivo, which is expected to help people gain physiological insights at single-cell level. However, trapping and manipulating single cells under crowded environments, such as blood vessels and lymph nodes, is still a challenging task. To overcome this issue, an annular beam formed by the far-field Bessel beam is introduced to serve as an optical shield to isolate the target cells from being disturbed. With this scheme, we successfully trapped and manipulated single blood cells in a crowded environment. Furthermore, we demonstrated manipulation of two lymphocytes ejected from a lymph node independently with dual-trap optical tweezers, which paves the way for exploring cell interactions under living conditions. Such technique might be helpful in the study of how natural killer cells response to virus-infected cells or tumor cells.